How relationship-maintenance strategies influence athlete burnout: Mediating roles of coach-athlete relationship and basic psychological needs satisfaction - Fan, F.; Chen, J.; Chen, Y.; Li, B.; Guo, L.; Shi, Y.; Yang, F.; Yang, Q.; Yang, L.; Ding, C.; Shi, H. (Frontiers in Psychology, 2023)
Introduction: Athlete burnout has many potential negative effects on athletes` sporting performance and careers. Maintaining and promoting the coach-athlete relationship to meet athletes` basic psychological needs is one way to reduce burnout. Existing studies of the correlation between coach-athlete relationships and athlete burnout have mainly focused on the coaches` leadership style, with little attention given to relationship-maintenance strategies and the mechanism of athlete burnout from the athletes` perspective.